Acidotolerant Bacteria and Fungi as a Sink of Methanol-Derived Carbon in a Deciduous Forest Soil - Morawe, Mareen; Hoeke, Henrike; Wissenbach, Dirk K.; Lentendu, Guillaume; Wubet, Tesfaye; Kröber, Eileen; Kolb, Steffen (Frontiers in Microbiology, 2017)
Methanol is an abundant atmospheric volatile organic compound (VOC) that is released from both living and decaying plant material. In forest and other aerated soils, methanol can be consumed by methanol-utilizing microorganisms that constitute a known terrestrial sink. However, the environmental factors that drive the biodiversity of such methanol-utilizers have been hardly resolved. Soil-derived isolates of methanol-utilizers can also often assimilate multicarbon compounds as alternative substrates. Here, we conducted a comparative DNA stable isotope-probing (SIP) experiment under methylotrophic (only [13C1]-methanol was supplemented) and combined substrate conditions ([12C1]-methanol and alternative multi-carbon [13Cu]-substrates were simultaneously supplemented) to (i) identify methanol-utilizing microorganisms of a deciduous forest soil (European beech dominated temperate forest in Germany), (ii) assess their substrate range in the soil environment and (iii) evaluate their trophic links to other soil microorganisms. The applied multi-carbon substrates represented typical intermediates of organic matter degradation, such as acetate, plant-derived sugars (xylose and glucose), and a lignin-derived aromatic compound (vanillic acid). An experimentally induced pH shift was associated with substantial changes of the diversity of active methanol-utilizers suggesting that soil pH was a niche-defining factor of these microorganisms. The main bacterial methanol-utilizers were members of the Beijerinckiaceae (Bacteria) that played a central role in a detected methanol-based food web. A clear preference for methanol or multi-carbon substrates as carbon source of different Beijerinckiaceae-affiliated phylotypes was observed suggesting a restricted substrate range of the methylotrophic representatives. Apart from Bacteria, we also identified the yeasts Cryptococcus and Trichosporon as methanol-derived carbon-utilizing fungi suggesting that further research is needed to exclude or prove methylotrophy of these fungi.